2022
DOI: 10.1002/jbm.b.35144
|View full text |Cite
|
Sign up to set email alerts
|

Injectable extracellular matrix hydrogels contribute to native cell infiltration in a rat partial nephrectomy model

Abstract: Decellularized extracellular matrix (dECM) hydrogels have cytocompatibility, and are currently being investigated for application in soft tissues as a material that promotes native cell infiltration and tissue reconstruction. A dECM hydrogel has broad potential for application in organs with complex structures or various tissue injury models.In this study, we investigated the practical application of a dECM hydrogel by injecting a kidney-derived dECM hydrogel into a rat partial nephrectomy model. The prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In this study, we showed that the proliferative activity was higher in 4 mg/ml gels than in gels of higher concentrations. We previously reported that different ECM concentrations change the elasticity of the scaffold and the pore size of the fiber structure 28 , and these mechanical properties may also serve as external signals to influence cell infiltration and/or metabolism 58 . However, given the multi-component nature of decellularized hydrogels, these mechanical factors are so complex and interdependent that concluding how individual properties may affect the behavior of MSCs was difficult in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we showed that the proliferative activity was higher in 4 mg/ml gels than in gels of higher concentrations. We previously reported that different ECM concentrations change the elasticity of the scaffold and the pore size of the fiber structure 28 , and these mechanical properties may also serve as external signals to influence cell infiltration and/or metabolism 58 . However, given the multi-component nature of decellularized hydrogels, these mechanical factors are so complex and interdependent that concluding how individual properties may affect the behavior of MSCs was difficult in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The fixed samples were then embedded in paraffin and subsequently sectioned to 0.5 µm thickness. Sections were subjected to hematoxylin and eosin (H&E) and AZAN staining as previously described 28 . In an immunohistological analysis, the sections were deparaffinized and rehydrated, and the antigens were retrieved.…”
Section: Methodsmentioning
confidence: 99%
“…The L-ECM was prepared according to a previous report, with some modi cations [24] [50]. Brie y, livers were removed from the disinfected peritoneal cavity of pigs, frozen at − 80°C, and thawed at 4°C for over 24 h for the freeze-thaw process, a common initial decellularization step.…”
Section: Decellularization Of Porcine Livermentioning
confidence: 99%
“…Kidney-derived decellularized ECM hydrogels have also been reported to enhance vascularization. [23] [24] In this study, we hypothesized that a decellularized liver hydrogel contributes to the survival of transplanted hepatocytes and the expression of their inherent functions via enhanced self-organization and vascularization. Here, we developed a liver-derived extracellular matrix (L-ECM) gel that functions as a scaffold material and investigated the orthotopic transplantation of mature hepatocytes in a brotic liver model.…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis is another important factor in hepatocyte engraftment 24 , and is related to the long-term engraftment of transplanted hepatocytes 25 . Kidney-derived decellularized ECM hydrogels have also been reported to enhance vascularization 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%